MOTIVATIONAL METHODS OF TEACHING TEXTUAL ANALYSIS OF NAVOI'S WORKS IN SECONDARY SCHOOLS. - Oimatova Nilufar Mirzhamolovna (Scholar Express Journal, 2022)
The article proposes methods that will help to analyze the text of the works of Alisher Navoi. These methods teach students to work with text, analyze.
Keywords: mystical term; poetic motive; interactive; methodological